Cardiac failure in patients treated with azacitidine, a pyrimidine analogue: Case reports and disproportionality analyses in Vigibase. Issue 5 (3rd February 2020) - Perino, Justine; Mottal, Nathan; Bohbot, Yohann; Servant, Vincent; Berroneau, Aude; Poustis, Pierre; Fenaux, Pierre; Laribi, Kamel; Charbonnier, Aude; Bilion, Emilien; Calmettes, Claire; Bégaud, Bernard; et al.
Abstract : Aims: Azacitidine (AZA), a pyrimidine analogue, is validated for high‐risk myelodysplastic syndrome or low‐blast acute myeloid leukaemia in unfit patients for more intensive treatment. This study assessed the putative link between cardiac failure (CF) and AZA exposure. Methods: Cases of CF in patients treated with AZA were retrospectively collected and described from several centres of the Groupe Francophone des Myélodysplasies. A description analysis and a disproportionality analysis using Vigibase, the WHO Global Individual Case Safety Reports (ICSRs) database, were conducted on ICSRs by the Standardized MedDRA Queries (SMQ broad) cardiac failure and by preferred terms cardiac failure and cardiac failure acute. The reported odds ratio (ROR) and its 95% 2‐sided confidence interval was computed by comparing the proportion of CF reports with the suspected drug (AZA) and the proportion of reports of the same adverse drug reaction with all other suspected drugs in the database during the same period. Results: In the 4 case reports, all patients presented a cardiovascular history. In 1 patient, CF recurred after AZA re‐challenge. The pharmacovigilance analysis in Vigibase retrieved 307 ICSRs of CF (SMQ) with AZA. Significant disproportionality signals associated with AZA were identified by using the SMQ cardiac failure (ROR 1.3) and the preferred terms cardiac failure (ROR 5.1) and cardiac failure acute (ROR 23.2). Conclusion: This study points to the potential role of AZA in the occurrence of CF. Cardiac evaluation before AZA initiation and regular monitoring of cardiac function during AZA treatment should be performed in patients with a history of cardiovascular disease.